Academic research – a catalyst for the innovation process within companies in Romania - Rodica Pamfilie; Smaranda Giusca; Robert Bumbac (Amfiteatru Economic Journal, 2014)
Current economic developments make the use of scientific resources, especially academic research, to be no longer just an option for companies wanting to remain competitive, but a necessity. This statement is based on the research conducted by the authors during the last three years on the companies' performance in Romania regarding the results of the innovation process and capitalization on scientific resources in order to improve this vital process. To achieve this, a mechanism should be created, through which key players in the market - companies, universities, research institutes and government - could work together towards the common goal of economic growth. This mechanism would help companies move beyond incremental innovation by using knowledge generated by universities or research institutes.
Keywords: I23; O32; M10; 330; academic research; innovation; research and development; companies